1998
DOI: 10.1073/pnas.95.18.10809
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of fullerenes: Antibodies specific for fullerenes and their characteristics

Abstract: The recent interest in using Buckminsterfullerene (fullerene) derivatives in biological systems raises the possibility of their assay by immunological procedures. This, in turn, leads to the question of the ability of these unprecedented polygonal structures, made up solely of carbon atoms, to induce the production of specific antibodies. Immunization of mice with a C 60 fullerene derivative conjugated to bovine thyroglobulin yielded a population of fullerene-specific antibodies of the IgG isotype, showing tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(137 citation statements)
references
References 28 publications
2
131
2
Order By: Relevance
“…For example, the facecentered-cubic C 60 without polar groups is capable of specific interactions with antibodies. 42 Previous studies have stated that the most important factors of nanoparticle-based interactions include van der Waals forces, hydrophobicity, p-interactions, and high spherical or cylindrical symmetry of nanoparticles, and more importantly, enthalpy driven effects of these factors for nanoparticles with other organic molecules were much larger than standard molecular systems. 43 Given this, one can therefore speculate that nanoparticles, especially C 60 , might form hybrid bimolecular complexes with P-gp with relatively high binding affinities, and thus could not be pumped by the protein as normal substrates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the facecentered-cubic C 60 without polar groups is capable of specific interactions with antibodies. 42 Previous studies have stated that the most important factors of nanoparticle-based interactions include van der Waals forces, hydrophobicity, p-interactions, and high spherical or cylindrical symmetry of nanoparticles, and more importantly, enthalpy driven effects of these factors for nanoparticles with other organic molecules were much larger than standard molecular systems. 43 Given this, one can therefore speculate that nanoparticles, especially C 60 , might form hybrid bimolecular complexes with P-gp with relatively high binding affinities, and thus could not be pumped by the protein as normal substrates.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the mouse immune repertoire is diverse enough to recognize and produce antibodies specific for fullerenes (15). We have now succeeded in isolating several monoclonal anti-C 60 antibodies.…”
mentioning
confidence: 94%
“…BALB͞c mice were immunized and boosted as described previously (15). Five days before the fusion, the mice were injected i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Potential applications for fullerenes include: use as optical limiters and photoconductors, for film growth and patterning, as catalysts for organic reactions, for hydrogen and energy storage, in lubrications and separations [76], and in extractions and purifications [58]. More specifically, biological applications have been proposed including use in AIDS and cancer treatment [77] and to make immunological antibodies [78], its electrical properties make them good candidates to be superconductors [59] and electronic transistors [79,80], and it has been used as a precursor molecule for nanocrystalline diamond film growth through chemical vapor deposition [81]. On a commercial basis, The Goodyear Tire and Rubber Company has obtained a patent for the use of fullerenes and fullerenic soot in the production of curable and vulcanized rubber indicating that the rubber made from these raw materials is superior to that manufactured from ordinary carbon black [82].…”
Section: Applicationsmentioning
confidence: 99%